Purification of hafnium from oxygen and nitrogen - Pylypenko, M.M.; Drobyshevskaya, A.A. (Физическая инженерия поверхности, 2013)
Data on the influence content of interstitial impurities on the mechanical properties of hafnium are
presented in this work. Investigations the purification of hafnium from oxygen at added of aluminum
on the melting reduction stage with subsequent refining electron beam melting were performed. It is
shown that vacuum thermal treatment of hafnium tetrafluoride before carrying out melting reduction
reduces the nitrogen content in hafnium less than 0.005 wt.%. В работе приведены данные по влиянию содержания примесей внедрения на механические
свойства гафния. Выполнены исследования по очистке гафния от кислорода при введении
алюминия на стадии восстановительной плавки с последующей рафинирующей электроннолучевой плавкой. Показано, что вакуум-термическая обработка тетрафторида гафния перед
проведением восстановительной плавки обеспечивает снижение содержания азота в гафнии
меньше 0,005 мас.%. В роботі приведені дані щодо впливу вмісту домішок проникнення на механічні властивості
гафнію. Виконано дослідження з очищення гафнію від кисню при введенні алюмінію на стадії
відновлювальної плавки з подальшою електронно-променевою плавкою. Показано, що вакуумтермічна обробка тетрафториду гафнію перед проведенням відновлювальної плавки забезпечує
зниження вмісту азоту в гафнії менше 0,005 мас.%.